The transcriptional regulation of the zeta-globin gene - Liu, S (2022)
The ζ-globin gene (HBZ in humans and Hba-x in mice) is the embryonic α-like globin gene that is expressed at the early stages of primitive erythropoiesis but silenced in the definitive erythroid lineage. Understanding the regulation of ζ-globin transcription, especially the mechanisms by which it is silenced, would shed light on gene regulation and offer therapeutic opportunities for ζ-globin induction in patients with severe α-thalassemia.